Achievement Goals and Creativity: Self‐Construal as an Antecedent. (31st May 2021) - Wang, Ling; Xu, Huihui; Yang, Dan; Tian, Heng; Xi, Rongrong; Du, Kaiye; Shi, Baoguo; Luo, Zheng
Abstract: The present study aimed to investigate the relationship among self‐construal, achievement goals, and creativity. A total of 464 junior high school students (mean age = 12.81 years; 44.2% male; 51.8% in seventh grade; and 48.2% in eighth grade) completed the Self‐Construal Scale, Goal Orientation Scales, Divergent Feeling Scale, and Kirton's Adaption–Innovation Inventory. Correlation analyses showed that two types of self‐construal were positively correlated with mastery goals, performance‐approach goals, and creativity indexes (i.e., creative personality and innovative cognitive style); in addition, mastery goals and performance‐approach goals were positively correlated with both creativity indexes, while performance–avoidance goals were positively correlated only with creative personality. Structural equation modeling revealed that independent self‐construal positively predicted creativity; moreover, both independent self‐construal and interdependent self‐construal positively predicted mastery goals, and mastery goals positively predicted creativity, which suggests that both types of self‐construal show positive indirect prediction for creativity through the mediation of mastery goals. In general, self‐construal could predict creativity through achievement goals.